Expert System For Major Selection Determination At Universitas Muhammadiyah Sinjai - Nurhikmayana Janna; Ingrid Nurtanio; Imran Taufiq (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2023)
The choice of major is very important to support the success of students in completing their studies well and on time. However, this is an important issue because, based on research by the Indonesia Career Center Network (ICCN) in 2017, 87 % of Indonesian students admit that the majors they chose do not suit their interests. And 71.7 % of workers have a profession that is not in accordance with their education. The obstacle faced by prospective students when choosing a major is that they do not know their interests, talents, and potential. Therefore, a system was created that could provide suggestions for majors that match the interests of prospective students. An expert system with the forward chaining method is used in the system. The method used in making this expert system application is the forward chaining method. This expert system process accepts the choices that are already available and have been filled in by the user. And the results of this expert system provide a solution for selecting majors based on the interests of prospective students. So that prospective students can determine the right major. From the results of the implementation and trials that have been carried out by researchers, a probability value is obtained that reaches 100 %, indicating that the system is functioning properly, and as many as 94 % of respondents stated that they strongly agree that the use of this application can help make it easier to determine majors at Universitas Muhammadiyah Sinjai.